Anxiety Disorder Pada Kesehatan Mental Anak: Studi Kasus Pada Akun Media Sosial Instagram - Wicaksono, Ardhy; Habibi, Muhammad Ilham (PT Literasi Nusantara Publisher, 2025)
This study aims to investigate the effect of interpersonal communication on children's mental health, with a focus on case studies on Instagram social media accounts. This research was conducted by Group 10 in the MPKK course at the Faculty of Communication Sciences, Muhammadiyah University Jakarta, with the supporting lecturer, Mrs. Nani Nurani. This research uses a qualitative approach with the FGD (Focus Group Discussion) method to obtain primary data from informants who become research informants. Secondary data was obtained from previous research relevant to this topic. The results of previous studies have shown that the use of social media, including Instagram, can contribute to the development of anxiety disorder in adolescents. Excessive use of social media can increase feelings of dissatisfaction with oneself, feelings of inferiority, social anxiety, and psychological pressure which can cause symptoms of anxiety disorder. However, not all teenagers who use Instagram will develop an anxiety disorder, because many other factors affect the risks and impacts of using social media. This research will be conducted online in Jakarta on July 10, 2023. The research method used is FGD with informants who have experience related to the influence of interpersonal communication and children's mental health. The data obtained will be analyzed to understand the role of interpersonal communication in children's mental health and how much influence it has on a person's mental health.